Increased risk of rhabdomyolysis in patients using statins: a population-based case-control study - Ya-Wen Lu; Jong-Yi Wang; Heng-Jun Lin; Wei-Sheng Chung (Therapeutic Advances in Drug Safety)
Background: Statins have been demonstrated to decrease cardiovascular events in high-risk patients. Statin-induced myotoxicity is a major contributor to statin intolerance and often the leading cause of statin discontinuation. Studies on the association between statin use and rhabdomyolysis risk remain limited. Objectives: This study aimed to compare the risk of rhabdomyolysis in patients who used statins versus those who did not. Design: A population-based case-control study was conducted. Methods: Data were collected from the Taiwan National Health Insurance Research Database between 2011 and 2020, involving 186,604 individuals with rhabdomyolysis and 746,416 without. Each patient with rhabdomyolysis (case group) was matched with four control patients based on the index year. Statins were assessed in both groups. Results: Approximately 50% of study participants were male, with an average age of 53 years. After confounding variables were adjusted for, patients who used statins exhibited a higher risk of rhabdomyolysis than those who did not (adjusted odds ratio (OR): 1.70, 95% confidence interval (CI): 1.68–1.73). Psychiatric disorders, alcoholism, generalized epileptic seizure, heat stroke, and crush injury were independent risk factors of rhabdomyolysis. Patients with psychiatric disorders who used statins exhibited a substantial risk of rhabdomyolysis (adjusted OR: 2.30, 95% CI: 1.95–2.71) compared with the reference group of patients without psychiatric disorders who did not use statins. Conclusion: Statin use was associated with a higher risk of rhabdomyolysis, and patients with psychiatric disorders who used statins exhibited an additive risk of rhabdomyolysis. These findings emphasize the need for clinicians to remain attentive to the potential risk of rhabdomyolysis in patients prescribed statins, especially in those with psychiatric disorders. Proactive monitoring, early recognition of symptoms, and individualized risk-benefit assessments are crucial to optimize treatment outcomes while minimizing adverse effects.